2007
DOI: 10.1111/j.1600-0714.2007.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

An orthotopic floor‐of‐mouth model for locoregional growth and spread of human squamous cell carcinoma

Abstract: The molecular investigation of head and neck cancer targets requires the utilization and optimization of established animal models to characterize the effects of gene transcription and protein expression on invasion and metastasis. Floor-of-the-mouth murine models have been developed to study tumor growth, invasion, and metastasis of murine squamous cell carcinoma (SCC) cells in immunocompetent mice and invasion and metastasis of human SCC cells in nude mice. However, there are tumor cell lines that do not pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…After injection into the masseter muscle of nude mice, BHY cells developed into highly differentiated squamous cell carcinomas which invaded the mandible, indicating that cathepsin L might help to degrade the bone matrix. This orthotopic animal model, in which tumour cells are injected adjacent to the mandible itself, has been used frequently in early studies of bone invasion [30]. However, based on our lab experience, injecting through the masseter muscle can cause discomfort and feeding difficulties for the animals, Fig.…”
Section: Cathepsinsmentioning
confidence: 98%
“…After injection into the masseter muscle of nude mice, BHY cells developed into highly differentiated squamous cell carcinomas which invaded the mandible, indicating that cathepsin L might help to degrade the bone matrix. This orthotopic animal model, in which tumour cells are injected adjacent to the mandible itself, has been used frequently in early studies of bone invasion [30]. However, based on our lab experience, injecting through the masseter muscle can cause discomfort and feeding difficulties for the animals, Fig.…”
Section: Cathepsinsmentioning
confidence: 98%
“…SCC cells were transfected with pcDNA and pcDNA-FLAG-Rap1GAP plasmids and mixed clonal populations with high Rap1GAP expression were selected in the presence of G418 (250 Ag/mL). The SCC cell line was previously identified as UM-SCC-11A (4,23), but recent genotyping confirmed that it is instead a UM-SCC-1 derivative, an independent cell line from UM-SCC-11A. 6 Two independently transfected mixed clonal populations, one pair (c2 and rg2) transfected by electroporation and the other pair (c1 and rg1) transfected by Lipofectamine, were used, as isolation of multiple single clones was unsuccessful after repeated attempts.…”
Section: Methodsmentioning
confidence: 99%
“…Work with mice includes both human HNSCC xenografts injected into immunocompromised animals, and immunocompetent animals injected with syngeneic cells [47]. Once tumors are established, they are assessed for growth or proliferation with bioluminescence imaging, 3D visualization through micro-computed topography, or excision followed by light microscopy [48, 49]. The more commonly used approaches will be discussed here, as well as some new in vivo assays.…”
Section: In Vivo Assaysmentioning
confidence: 99%